Recent advancements in management of gastrointestinal tuberculosis - Khan, Basim F.; Basha, Ahmed M.; Bakhurji, Bandar R.; Aldossari, Bader J.; Alsumaihi, Abdulaziz S.; Sherif, Sherif A. (International Journal Of Community Medicine And Public Health, 2018)
Abdominal tuberculosis and its protean manifestations still create a worldwide diagnostic challenge for clinicians and remain an important concern in the developing world. Crohn’s disease, which is being increasingly recognized in countries where intestinal tuberculosis is prevalent, needs to be differentiated as the two diseases resemble each other in their clinical presentation, and in their radiological, endoscopic, and histological findings. New diagnostic modalities and scoring systems have facilitated the differentiation of Crohn’s disease from intestinal tuberculosis with good accuracy. Randomized trials have shown 6 months of therapy to be equivalent to longer durations of treatment for patients with abdominal tuberculosis.